The Learning Economy and the Economics of Hope - Lundvall, Bengt-Åke (Anthem Studies in Innovation and Development, 2016)
'The Learning Economy and the Economics of Hope' offers original insights in processes of innovation and learning and draws implications for economic theory and public policy. The book introduces the reader to important concepts such as innovation systems and the learning economy. It throws new light on economic development and opens up horizons for a new kind of economics - the economics of hope.